Risk factors of thromboembolism in nephrotic syndrome - XU Qing; WAN Jian-xin (Linchuang shenzangbing zazhi)
Objective To investigate the risk factors of thromboembolism complications in patients with nephrotic syndrome.Methods The clinical data of 592 cases of nephrotic syndrome who received the treatment in The Frist Hospital of Fujian Medical Universty from January 2002 to December 2010 were retrospectively analyzed,including name,sex,age,systolic blood pressure,diastolic blood pressure,past medical history(including the history of diabetes,the history of hypertension and the history of cancer),clinical manifestations(including soreness of waist,macroscopic haematuria,usage of diuretics)and clinical laboratory results[including platelet(PLT)counts,serum albumin(Alb),blood urea nitrogen(BUN),serum creatinine(CREA),blood uric acid(UA),blood total cholesterol(TCHO),triglyceride(TG),low-density lipoprotein cholesterol(LDL-C),very low-density lipoprotein cholesterol(VLDL),serum calcium(Ca),fibrinogen(FIB).The patients were divided into two groups:thromboembolism group and non thromboembolism group.The risk factors of thromboembolism in patients with nephrotic syndrome were analyzed.Results The incidence of thromboembolism was 3.71%in592 patients with primary nephrotic syndrome,inculuding 17 cases of venous thrombosis and 6 cases of arterial thrombosis,among which1 case had both arterial thrombosis and venous throm-bosis.As compared with non thromboembolism group,the patients were older,systolic blood pressure was higher and the number of platelet counts less in thromboembolism group.The incidence of thromboembolism in patients having the history of hypertension and cancer was significantly increased.The multifactor Logistic regression analysis showed that the history of cancer and the history of hypertension were the independent risk factors of thromboembolism in patients with nephrotic syndrome.Conclusions The history of cancer and the history of hypertension are the independent risk factors of thromboembolism in patients with nephrotic syndrome.